EVALUASI ANTIBAKTERI DAN ANTIOKSIDAN EKSTRAK SMILAX spp. DARI PULAU ENGGANO - Praptiwi Tiwi; Kartika Dyah Palupi; Ahmad Fathoni; Ary P Keim; M Fathi Royani; Oscar Effendi; Andria Agusta (BERITA BIOLOGI, 2016)
Three species of Smilax spp. (Smilax macrophylla, S. odoratissima and S. zeylanica) collected from Enggano island were evaluated for their potential as an antibacterial and antioxidant. Stems and leaves of three species of Smilax spp. were extracted successively with nhexane,chloroform, ethyl acetate and methanol. Antibacterial activity was evaluated by TLC-bioautography against Eschericha. coli InaCC B5 and Staphylococcus. aureus Ina-CC B4. The antioxidant activity was analyzed by DPPH free radical activity by bioautography method. The value of minimum inhibitory concentration (MIC) and IC50 of active extracts were done by serial dilution in 96- well microplate. The results showed that 20 extracts have antioxidant activity, 13 extracts inhibited the growth of S. aureus Ina-CC B4, and 14 extracts inhibited the growth of E. coli Ina-CC B5. MIC values of active extracts against S. aureus Ina-CC B4 were in the range of 128 - > 512 µg / ml, while the values of MIC against E. coli B5 Ina-CC were > 512 µg / ml. IC50 values of extracts that has antioxidant activity were in the range of 184.11-4549.34 mg/L.